(untitled) (Signifiances (Signifying), 2022)
We investigate more than a thousand instances of the construction very New York produced by insiders and outsiders on Twitter. The analysis bears on constructional, semantico-pragmatic, and metalinguistic features. Amongst other things, we find that the construction has typically positive valence and is used to exploit a rich but recurring set of mental representations (e.g. fashion, food). Crucially, we show using multinomial regression that insider-outsider status predicts several of the construction’s linguistic features, even when considering users’ sociodemographic characteristics. These results suggest that users’ relationship with the semioreferential object “New York” likely influences their ways of imbuing the construction with meaning. The study underscores the relevance of characterizing online corpora’s contributors in detail when investigating semantic phenomena.